Retrospective single-center analysis of the reasons and serious complications of peritoneal-related peritonitis in patients with end-stage renal disease undergoing peritoneal dialysis treatment - Grzebalska, Agnieszka M.; Steć, Anna; Ławnicka, Izabela; Bednarek-Skublewska, Anna; Książek, Andrzej (Polish Journal of Public Health, 2019)
Introduction. Peritonitis is still a serious complication of peritoneal dialysis (PD). Consequences of peritonitis can be severe. The most severe are peritoneal dialysis discontinuation and patient’s death. In majority, peritonitis is bacterial in the origin. Mainly there is a gram-positive infection, less commonly gram-negative one. Some peritonitis are culture-negative, because of former antibiotics use. In minority, fungal, tuberculous or even viral peritonitis are observed.Aim. The aim of the present study is to analyze the number, origin and serious complications of peritoneal-related peritonitis cases found in our PD center.Material and methods. We performed a retrospective five-years evaluation of medical records. The total number of peritonitis episodes was 56 cases, underwent by 30 adult patients on chronic peritoneal dialysis. Peritonitis was diagnosed according to ISPD recommendations. Causes and serious complications of peritoneal-related peritonitis were analyzed in every single year. Etiology of peritonitis was classified on the basis of the result of effluent dialysate culture as: gram-positive, gram-negative and culture negative. Peritoneal dialysis discontinuation or patient’s death were defined as serious complications.Results. Among 56 cases of peritoneal-related peritonitis 44.6% were gram-positive, 26.8% gram-negative and 28.6% culture-negative. No fungal or tuberculosis peritonitis were found. Because of the peritonitis complications in the evaluated period, six patients discontinued peritoneal dialysis and were switched to hemodialysis (20%), two others died (6.7%).Conclusion. The further improvement in peritonitis’ causes identification and treatment is needed in order to reduce number of serious complications in our medical center.